PENGARUH TINGKAT EFISIENSI DAN LEVERAGE TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Prasetia, Maftuhin Agung; Trihastuti, Adiati (Universitas Muhammadiyah Metro, 2026)
This study aims to understand the extent to which operational efficiency and debt-based funding structures shape the financial performance of companies in the food and beverage subsector listed on the Indonesia Stock Exchange during 2019–2023. Efficiency is measured using OER, COGS, and TATO indicators, while DAR and DER are used to describe leverage. Financial performance is estimated through return on assets (ROA) and return on equity (ROE). The analysis was conducted using a quantitative approach based on secondary data from the financial statements of 17 companies selected through purposive sampling, resulting in a total of 85 observation units. Model testing utilized Structural Equation Modeling—Partial Least Squares (SEM-PLS) supported by SmartPLS 4 software. The model evaluation results indicate that efficiency is significantly negatively correlated with financial performance; surges in cost burdens and weakening asset productivity directly depress profitability. Conversely, leverage does not show a statistically significant relationship with profitability, suggesting that fluctuations in debt levels have not been strong enough to change financial performance throughout the study period. Overall, cost efficiency emerged as the most dominant determinant in shaping financial results in the food and beverage subsector in the context of this study.